2005
DOI: 10.1016/j.ijindorg.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Price wars and collusion in the Spanish electricity market

Abstract: We analyze the time-series of prices in the Spanish electricity market by means of a time varyingtransition-probability Markov-switching model. Accounting for changes in demand and cost conditions (which reflect changes in input costs, capacity availability and hydro power), we show that the time-series of prices is characterized by two significantly different price levels. Using a Cournot model among contracted firms, we characterize firms' optimal deviations from a collusive agreement, and identify trigger v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 34 publications
(34 reference statements)
3
90
0
7
Order By: Relevance
“…Business press and academic research have reported on price wars in industries including electricity (Fabra and Toro 2005), oil (Slade 1992) (Elzinga and Mills 1999;Mil grom and Roberts 1982). Other factors deemed to be induc tive to price wars are declining economic conditions (Eilon 1993;Slade 1990) and, often related to this, consumers' low (and/or declining) brand loyalty and high (and/or increas ing) price sensitivity (Klemperer 1989;Sairamesh and Kephart 2000).…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…Business press and academic research have reported on price wars in industries including electricity (Fabra and Toro 2005), oil (Slade 1992) (Elzinga and Mills 1999;Mil grom and Roberts 1982). Other factors deemed to be induc tive to price wars are declining economic conditions (Eilon 1993;Slade 1990) and, often related to this, consumers' low (and/or declining) brand loyalty and high (and/or increas ing) price sensitivity (Klemperer 1989;Sairamesh and Kephart 2000).…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…There is a wide consensus on the risks of the market clearing mechanism used, as it may facilitate collusion. Fabra and co-authors (Fabra, 2003;Fabra et al 2006a;Fabra and Toro, 2006b) argue that the auction used to clear the market increases the ability of firms to sustain over-competitive prices. Ciarreta and Gutiérrez-Hita (2006), Espinosa (2009), andMarin andGarcia-Diaz (2003) reach similar conclusions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Spain and Portugal, VPPs have also been used in an attempt to make the market more competitive. For a description and analysis of VPPs, see Ausubel and Cramton (2010), Federico and Ló pez (2009) and Schultz (2009). Some unconventional forms of forward contracts have been used in other competition policy settings, such as certain voluntary operating restrictions adopted by firms in antitrust lawsuits, see Borenstein (1996).…”
Section: Introductionmentioning
confidence: 99%